Establishment of the national reference standard for tetanus toxoid in Thailand. (March 2020) - Pittayakhajonwut, Daraporn; Ekthaicharern, Pannipa; Hommalai, Greanggrai; Lohavech, Dissaya; Jongkol, Rattana; Poredi, Indrajeet; Harjee, Nadir; Amen, Assajun; Suppasansathorn, Apichai; Phumiamorn, Supaporn
Abstract: The use of reference materials is the basis of standardization and quality control of biologicals such as vaccines produced by different manufacturers and lot-to-lot consistency. The aim of this study was to establish a secondary local and national reference standard of adsorbed tetanus toxoid that can be used for tetanus toxoid vaccine potency testing. Concentrated bulk of tetanus toxoid was adjuvanted and aliquoted before lyophilization. Lyophilized product was tested for biological and physicochemical qualities, including moisture content, identity, appearance, antigen content, degree of adsorption, and sterility. The potency of the candidate reference material was calibrated against the 4th World Health Organization International Standard (WHO IS) for tetanus toxoid by two independent laboratories (BioNet-Asia and Thai National Control Laboratory) using the WHO mouse challenge test. A total of 839 vials with lyophilized tetanus toxoid reference material were produced. Potency was estimated at 115 IU/vial [intra-laboratory geometric coefficient of variation (GCV) of 7 tests was 16.5%] and 112 IU/vial (intra-laboratory GCV of 5 tests was 38.6%) at the two laboratories, with an inter-laboratory GCV of 25.5%. The potency of the candidate standard was assigned a value of 114 IU/vial. The candidate reference standard was approved by The Thai National Central Laboratory (NCL) as the Thai national tetanus toxoid reference standard.